2021
DOI: 10.1109/tte.2020.3014688
|View full text |Cite
|
Sign up to set email alerts
|

Modified Particle Swarm Optimization With Chaotic Attraction Strategy for Modular Design of Hybrid Powertrains

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document.When citing, please reference the published version. Take down policyWhile the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Zhou et al developed a modified accelerated particle swarm optimization (MAPSO) algorithm for modular design considering the design variables which are from discontinuously varying domains (e.g. integers) [29]. The results suggested that the proposed MAPSO can achieve global optimal results in a more computationally efficient manner compared to both Pareto methods (NSGA-II) and weighted-sum methods (PSO, APSO).…”
Section: Ai Methods For Powertrain Designmentioning
confidence: 99%
“…Zhou et al developed a modified accelerated particle swarm optimization (MAPSO) algorithm for modular design considering the design variables which are from discontinuously varying domains (e.g. integers) [29]. The results suggested that the proposed MAPSO can achieve global optimal results in a more computationally efficient manner compared to both Pareto methods (NSGA-II) and weighted-sum methods (PSO, APSO).…”
Section: Ai Methods For Powertrain Designmentioning
confidence: 99%
“…In this research field, heuristic algorithms are usually adopted to handle NP-complete issues. Recently, University of Birmingham proposed the improved evolutionary algorithm with chaos attractive policy for the energy management scheme design for on-road vehicles [3,4] and off-road vehicles [5]. However, these single-objective optical solutions are proven to be hard to build a Pareto frontier with good distribution, particularly for two or more objectives which need to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Metaheuristic algorithms (e.g. Generic Algorithms [33], [34] and Particle Swarm Optimization (PSO) algorithms [35], [36]) have been proposed to conduct global searches in learning conditions, and are more computationally efficient than exhaustive searching. The PSO algorithm, which mimics the intelligence of birds flocking, is one of the most widely used AI-learning algorithms in automotive engineering.…”
Section: Introductionmentioning
confidence: 99%